2012
DOI: 10.1016/j.neulet.2012.07.067
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic, but not static, pain sensitivity predicts exercise-induced muscle pain: Covariation of temporal sensory summation and pain intensity

Abstract: Cross-section studies suggest that measures of pain sensitivity, derived from quantitative sensory testing (QST), are elevated in persons with chronic pain conditions. However, little is known about whether development of chronic pain is preceded by elevated pain sensitivity or pain sensitivity increases as a result of prolonged experience of pain. Here we used QST to test static (single suprathreshold stimuli) and dynamic (temporal sensory summation) pain processing of thermal stimuli. Muscle pain was induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
4
13
2
Order By: Relevance
“…Further, prolonged experimental pain models, such as delayed-onset muscle soreness (DOMS) following unaccustomed eccentric exercise, can induce soreness lasting for several days, mimicking the deep, movement-evoked pain and functional impairment seen in mild non-specific LBP patients 6 . Prior experimental work has demonstrated that DOMS increases TSP magnitude over painful muscles 22,47 and in nearby regions 5 . However, changes in TSP over distant testing sites outside the painful region (which may better indicate central pain processing changes) as is assessed and often altered in clinical populations 65,66 , as well as changes in CPM, have not been investigated in this LBP-model.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, prolonged experimental pain models, such as delayed-onset muscle soreness (DOMS) following unaccustomed eccentric exercise, can induce soreness lasting for several days, mimicking the deep, movement-evoked pain and functional impairment seen in mild non-specific LBP patients 6 . Prior experimental work has demonstrated that DOMS increases TSP magnitude over painful muscles 22,47 and in nearby regions 5 . However, changes in TSP over distant testing sites outside the painful region (which may better indicate central pain processing changes) as is assessed and often altered in clinical populations 65,66 , as well as changes in CPM, have not been investigated in this LBP-model.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For instance, TSP and CPM, assessed pre-operatively in painfree patients undergoing thoracotomy, demonstrated predictive value in determining postoperative pain intensity 70,75 . TSP and CPM magnitude in people with pain conditions can also relate to the intensity of pain experienced 5,49,65 , suggesting fluctuations in TSP and CPM may be consequential to pain 2,15 . In line with this suggestion, clinical studies have demonstrated improvements in CPM and pain sensitivity following replacement of painful osteoarthritic joints 18,30 , and experimental studies have shown impaired CPM following painful saline injection 2 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The required equipment is available in many specialized pain centers. Many QST protocols are available [36][37][38][39], however they require further study, but its wider use may be hampered by its costs, complexity and time-consuming nature.…”
mentioning
confidence: 99%
“…In healthy volunteers, exercise-induced muscle soreness of the lower back was associated with higher heat-evoked pain ratings over lumbar dermatomes (Bishop et al 2012). Interestingly, dynamic pain processing, i.e.…”
Section: Discussionmentioning
confidence: 94%